Depletion of Soil Water-Extractable Organic Matter With Long-Term Coverage by Impervious Surfaces - Wang, Yinghui; Zhang, Qiang; Majidzadeh, Hamed; He, Chen; Shi, Quan; Kong, Sifang; Yang, Zhibing; Wang, Junjian (Frontiers in Environmental Science, 2021)
Water-extractable organic matter (WEOM) in soil is the critical substrate that fuels microbial-driven biogeochemical cycles. However, questions remain regarding whether and how expanding impervious surface area under global urbanization may alter soil WEOM cycling. Based on absorbance and fluorescence spectroscopy and Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS), we compared the content and chemical signatures of soil WEOM under impervious surfaces with those in adjoining open areas and evaluated the impacts of types (complete sealing by concrete and partial sealing by house structures) and durations (1.5, 27, and 114 years) of impervious surface coverage. The content of soil WEOM and its chromophoric and fluorescent fractions were not significantly changed (less than 20%) after 1.5 years of coverage by concrete and house structures. However, these parameters decreased by more than 30% with 27 and 114 years of coverage by the residential home structures. The microbial-humic-like and protein-like fluorescent WEOM persisted preferentially over the terrestrial-humic-like and nonfluorescent WEOM. FT-ICR MS results suggest various degrees of depletion of biochemical groups in WEOM. While the water-extractable lipid-like compounds increased with 1.5 years of coverage, all studied biochemical groups were depleted with long-term coverage, which might reduce the microbial processing of suberin-derived compounds. This study highlights the remarkable impacts of soil sealing on reducing substrate availability for microbial carbon processing in urban environments.